2018
DOI: 10.1111/mec.14709
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of local adaptation along environmental gradients in a range‐expanding damselfly (Ischnura elegans)

Abstract: Insect distributions are shifting rapidly in response to climate change and are undergoing rapid evolutionary change. We investigate the molecular signatures underlying local adaptation in the range-expanding damselfly, Ischnura elegans. Using a landscape genomic approach combined with generalized dissimilarity modelling (GDM), we detect selection signatures on loci via allelic frequency change along environmental gradients. We analyse 13,612 single nucleotide polymorphisms (SNPs), derived from restriction sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
130
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(142 citation statements)
references
References 104 publications
(253 reference statements)
11
130
1
Order By: Relevance
“…Spatial coordinates (latitude, longitude) and elevation were recorded for each site using a handheld GPS device (Garmin International). We implemented a paired‐gradient sampling design where possible, with at least two sites per latitudinal range (see Dudaniec, Yong, Lancaster, Svensson, & Hansson, ). This design is recommended to ensure representation of environmental heterogeneity with spatial replication (Rellstab et al, ), and is found to be more effective at detecting weak spatial selection in comparison with random or transect designs (Lotterhos & Whitlock, ).…”
Section: Methodsmentioning
confidence: 99%
“…Spatial coordinates (latitude, longitude) and elevation were recorded for each site using a handheld GPS device (Garmin International). We implemented a paired‐gradient sampling design where possible, with at least two sites per latitudinal range (see Dudaniec, Yong, Lancaster, Svensson, & Hansson, ). This design is recommended to ensure representation of environmental heterogeneity with spatial replication (Rellstab et al, ), and is found to be more effective at detecting weak spatial selection in comparison with random or transect designs (Lotterhos & Whitlock, ).…”
Section: Methodsmentioning
confidence: 99%
“…Our present analyses of genetic structure advance our understanding of the relative roles of selection, ecological events, and neutral processes as drivers of evolutionary divergence between populations of pygmy grasshoppers (Tinnert & Forsman, 2017;Tinnert, Hellgren et al, 2016) and other ecologically similar organisms. That neutral genetic differentiation between populations was associated with functional genetic differentiation (as revealed by Mantel test based on pairwise F ST values for neutral and outlier AFLP loci) might indicate that divergence in functional traits has not only been influenced by selection, but also by gene flow and stochastic processes associated with founder events and drift in small populations (Dudaniec et al, 2018;Leinonen, McCairns, O'Hara, & Merila, 2013;Tibblin et al, 2015). However, pairwise population genetic differentiation was more pronounced on average for outlier loci than for neutral loci, and sampling location accounted for a greater proportion of the total variance in outlier (32%) than in neutral (8%) AFLP loci, thus implicating also natural selection and local adaptation as drivers of population divergence (Dudaniec et al, 2018;Johansson et al, 2016;Landguth & Balkenhol, 2012;Quintela et al, 2014).…”
Section: Contrasting Environments-diversity In Disturbed and Stablementioning
confidence: 99%
“…Adaptive or functional genetic diversity is influenced by the same suite of processes discussed above for neutral diversity. In addition, functional diversity is affected by differential fitness among individuals within populations (Endler, ; Holderegger, Kamm, & Gugerli, ) and by divergent selection in populations that inhabit different environments, potentially leading to local adaptations and differentiation (Dudaniec, Yong, Lancaster, Svensson, & Hansson, ; Johansson, Quintela, & Laurila, ; Lenormand, ; Noguerales, García‐Navas, Cordero, & Ortego, ; Quintela, Johansson, Kristjansson, Barreiro, & Laurila, ; Zhi‐Xiang, Fang, & Guo‐Fang, ). Unlike neutral diversity, functional genetic and phenotypic variability can in turn have a positive impact on the fitness of populations, by increasing evolvability, dampening fluctuations, increasing production of dispersers (emigrants), improving establishment success, and reducing extinction (Forsman, ; Forsman, Ahnesjö, Caesar, & Karlsson, ; Forsman & Wennersten, ; Forsman, Wennersten, Karlsson, & Caesar, ; Hughes, Inouye, Johnson, Underwood, & Vellend, ; Mills et al., ; Reed & Frankham, ; Rius & Darling, ; Vergeer, Sonderen, & Ouborg, ; Wennersten & Forsman, ; Whitlock, ; Willi, Van Buskirk, & Hoffmann, ).…”
Section: Introductionmentioning
confidence: 99%
“…temporal climate variability in its new range (Lancaster et al 2015, Dudaniec et al 2018. Mating among differentially adapted genotypes also produces novel genotypes not present in either population before climate change.…”
Section: Introgressionmentioning
confidence: 99%